Clinical characteristics and molecular epidemiology of children with meningitis in Tehran, Iran: a prospective study. (November 2019) - Pormohammad, A.; Lashkarbolouki, S.; Azimi, T.; Gholizadeh, P.; Bostanghadiri, N.; Safari, H.; Armin, S.; Mohtavinejad, N.; Fallah, F.
Abstract: The molecular epidemiology of meningitis in children is unclear in Iran, and data are scarce. We aimed to characterize its clinical and paraclinical features as well as to determine the distribution of genotype/capsular types of common bacterial meningitis agents in children in Iran. All children suspected to have meningitis aged 4 days to 15 years were enrolled onto a prospective cross-sectional study from January 2015 to September 2017. Diagnostic values of clinical features, cerebrospinal fluid and serum parameters were evaluated independently and in combination with each other by multivariate logistic regression to develop a diagnostic rule. Genotype/capsular types of all the isolates were determined by targeting serotype-specific genes with uniplex or multiplex PCR. Among 119 patients suspected of having meningitis, 43 had bacterial meningitis, 19 aseptic and one tuberculous; and there were 56 nonmeningitis cases (NMC). Presentation of four features at the same time—cerebrospinal fluid white blood cell count, protein, polymorphonuclear leukocytes and serum C-reactive protein—revealed 100% sensitivity and 86.4% specificity for diagnosis of bacterial meningitis. Haemophilus influenzae type b (60%), Streptococcus pneumoniae serotype 3 (28.5%) and Neisseria meningitidis B (63.5%) were the most prevalent serotypes. This study demonstrated that a well-designed combination of clinical and paraclinical features is useful, but these combinations are not good enough to be relied on as stand-alone exclusionary tests for the diagnosis of bacterial meningitis. In addition, public immunization of infants with the most prevalent bacterial meningitis serotypes is recommended.